If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 8)(x + 4) = 0 Reorder the terms: (8 + 2x)(x + 4) = 0 Reorder the terms: (8 + 2x)(4 + x) = 0 Multiply (8 + 2x) * (4 + x) (8(4 + x) + 2x * (4 + x)) = 0 ((4 * 8 + x * 8) + 2x * (4 + x)) = 0 ((32 + 8x) + 2x * (4 + x)) = 0 (32 + 8x + (4 * 2x + x * 2x)) = 0 (32 + 8x + (8x + 2x2)) = 0 Combine like terms: 8x + 8x = 16x (32 + 16x + 2x2) = 0 Solving 32 + 16x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(16 + 8x + x2) = 0 Factor a trinomial. 2((4 + x)(4 + x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Subproblem 2
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Solution
x = {-4, -4}
| 27=9+x | | 2m^2-15m-27=0 | | -3m(n-2)=3n-5n+9 | | 6c+5u=-49 | | (x-67)+x=261 | | 3(2x-1)-(2-x)-7x=0 | | x+(x-1)=81 | | d^2-14=50 | | 4x^2+4y^2+16x-8y-5=0 | | 2r-rt+5t=1 | | z-3/4z+3/8=-3/8(z-7/2) | | -x+40=10+x | | -8(p+7)=8 | | 3(c-2)=5 | | 8(n-6)=-8 | | -5x-4y=23 | | -1.4v+2.3=-5.4v-5.7 | | 3(4m+m)=-75 | | 4y+6=-18 | | 3y=32 | | 5x-5/-10=70 | | 12(w+3w)=144 | | -u-19=-5u+13 | | x^6-14x^3=0 | | 18(x+2)+2x=17x+36 | | -2/5=-?m+3/5 | | (4-7j)(3-4j)= | | 6=-4(n-1) | | -2y+3=-4y-5 | | -5x+6y=120 | | -0.7x+2.69=-0.5x+3.49 | | 4x-3=x-2 |